2021
DOI: 10.1016/j.immuni.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells specific for an immunodominant SARS-CoV-2 nucleocapsid epitope display high naive precursor frequency and TCR promiscuity

Abstract: To better understand primary and recall T cell responses during COVID-19, it is important to examine unmanipulated SARS-CoV-2-specific T cells. Using peptide-HLA tetramers for direct ex vivo analysis, we characterized CD8 + T cells specific for SARS-CoV-2 epitopes in COVID-19 patients and unexposed individuals. Unlike CD8 + T cells directed towards subdominant epitopes – B7/N 257 , A2/S 269 and A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
165
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(203 citation statements)
references
References 51 publications
24
165
3
4
Order By: Relevance
“…SARS-CoV-2 reactive CD8+ T cells have been associated with milder disease 43 , and as previously mentioned, conflicting evidence has recently emerged regarding the presence of pre-existing CD8+ T cells in unexposed patients. Nguyen et al 16 ., found that SARS-CoV-2 CD8+ T cells in Australian pre-pandemic samples, including those recognising the immunodominant HLA-B*07:02-SPR* complex, predominately displayed a naïve phenotype, indicating a lack of pre-existing memory conferred by HCoV. In contrast, Francis et al 15 ., found that ~80% of unexposed individuals carrying HLA-B*07:02 show a pre-existing CD8+ T cell response to HLA-B*07:02-SPR*.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…SARS-CoV-2 reactive CD8+ T cells have been associated with milder disease 43 , and as previously mentioned, conflicting evidence has recently emerged regarding the presence of pre-existing CD8+ T cells in unexposed patients. Nguyen et al 16 ., found that SARS-CoV-2 CD8+ T cells in Australian pre-pandemic samples, including those recognising the immunodominant HLA-B*07:02-SPR* complex, predominately displayed a naïve phenotype, indicating a lack of pre-existing memory conferred by HCoV. In contrast, Francis et al 15 ., found that ~80% of unexposed individuals carrying HLA-B*07:02 show a pre-existing CD8+ T cell response to HLA-B*07:02-SPR*.…”
Section: Discussionmentioning
confidence: 98%
“…In these convalescent patients, it is unclear whether infection itself, and/or prior exposure to HCoVs are driving this subset of individuals to select for these peptides. There is conflicting evidence surrounding the existence of memory SARS-CoV-2 cross-reactive CD8+ T cells in unexposed individuals 15,16,40 , and a limitation of our work is that we could not to provide a direct link to pre-existing immunity, because from healthy donors the MIRA dataset only evaluated expanded naïve T cells and did not examine anti-viral efficacy of the responding T cells. Indeed, although we cannot determine the cause or timeframe of this selection of sCoV-2-HCoV peptides in this subset of individuals, the potential implications are interesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staining with MHCmultimers loaded with individual peptides is an alternative approach, but it requires pre-selection of immunogenic peptides. Several immunodominant SARS-CoV-2 epitopes presented by common HLA alleles were discovered in the past year, permitting the tracking of epitope-specific T cell response in infected (Francis et al 2021;Gangaev et al 2021;Schreibing et al 2021;Shomuradova et al 2020;Kared et al 2021;Saini et al 2021;Ferretti et al 2020;Nielsen et al 2021;Peng, Yanchun et al 2020;Rha et al 2021;Sekine et al 2020;Schulien et al 2021;Habel et al 2020;Nguyen et al 2021) and vaccinated (Thimme et al 2021;Sahin et al 2021) individuals using MHC-multimers. Although at the peak of the infection response reports have described more than 10% of CD8+ T cells specific to a single SARS-CoV-2 epitope (Saini et al 2021;Gangaev et al 2021), a month after infection the frequency of most epitope-specific T cell populations is typically less than 1% (Ferretti et al 2020;Peng, Yanchun et al 2020;Kared et al 2021;Rha et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most immunodominant CD8 epitopes identified so far is found within the SARS-CoV-2 nucleoprotein, 105-SPRWYFYYL-113 (N 105-113 ) [ 1 • , 2 • , 3 • , 4 , 5 • ]. The frequency of this epitope is potentially due to high frequency of naïve precursor T cells that can recognise this epitope [ 12 •• ]. Several other immunodominant epitopes for SARS-CoV-2 are predicted to exist.…”
Section: Introductionmentioning
confidence: 99%